$\displaystyle y = sec^2x - tan^2x $ any help with this one much appreciated..
Follow Math Help Forum on Facebook and Google+
Note that: $\displaystyle \color{blue} \sec ^2 x = 1 + \tan ^2 x$ So: $\displaystyle y \ = \ {\color{blue}\sec^2 x} - tan^2 x \ = \ {\color{blue}(1 + \tan^2 x)} - \tan^2 x \ = \ 1$
Originally Posted by o_O Note that: $\displaystyle \color{blue} \sec ^2 x = 1 + \tan ^2 x$ So: $\displaystyle y \ = \ {\color{blue}\sec^2 x} - tan^2 x \ = \ {\color{blue}(1 + \tan^2 x)} - \tan^2 x \ = \ 1$ thanks mate.
View Tag Cloud